STRATEGIES FOR ENHANCING FACULTY MOTIVATION: EVIDENCE-BASED PRACTICES FOR HIGHER EDUCATION INSTITUTIONS - Kayumova Muborak Abzal kizi (Labor economics and human capital, 2024)
This study investigates the factors influencing faculty motivation in higher education institutions in Uzbekistan, employing a mixed-methods approach that combines quantitative surveys and qualitative interviews. The research reveals that both intrinsic motivators, such as a passion for teaching and commitment to student success, and extrinsic factors, including salary and recognition, significantly impact faculty engagement. These findings underscore the importance of addressing both motivational dimensions to enhance overall productivity within the academic context. This research contributes to the existing literature by highlighting unique cultural and contextual factors affecting faculty motivation in Uzbekistan. Furthermore, evidence-based strategies derived from the study offer practical implications for higher education institutions aimed at improving faculty satisfaction and retention. Such enhancements are critical for fostering better educational outcomes and institutional success in Uzbekistan's evolving higher education landscape.